1986
DOI: 10.1037/0278-7393.12.3.432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elaborative processing on implicit and explicit memory for new associations.

Abstract: Previous research has demonstrated that priming effects on word-completion tests are influenced by newly acquired associations between normatively unrelated words. This phenomenon, which we call implicit memory for new associations, can occur independently of explicit remembering but requires elaborative processing of study materials. The present experiments explored further the relation between elaborative processing and implicit memory for new associations. Results indicated that implicit memory for new asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
249
7
5

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 235 publications
(285 citation statements)
references
References 50 publications
24
249
7
5
Order By: Relevance
“…A 2 x 2 analysis of variance (ANOVA) was performed on these data, but as a result of subject variability the Group x Context Condition interaction was not significant, F{\, 22) = 1.75, p = .19, MS C = 2.01. In fact, the effect of context exhibited by healthy control subjects, in both this experiment and in those of Graf and Schacter (1985;Schacter & Graf, 1986a), was quite small and amounted to about one more word completed in the same condition than in the different context condition. Figure 1 also shows performance by healthy control subjects in the no-cues condition.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…A 2 x 2 analysis of variance (ANOVA) was performed on these data, but as a result of subject variability the Group x Context Condition interaction was not significant, F{\, 22) = 1.75, p = .19, MS C = 2.01. In fact, the effect of context exhibited by healthy control subjects, in both this experiment and in those of Graf and Schacter (1985;Schacter & Graf, 1986a), was quite small and amounted to about one more word completed in the same condition than in the different context condition. Figure 1 also shows performance by healthy control subjects in the no-cues condition.…”
Section: Resultsmentioning
confidence: 94%
“…For example, priming of new associations in normal subjects occurs only if the study task ensures elaborative encoding of the new associations (Schacter & Graf, 1986a). In contrast, repetition priming is not affected or only slightly affected by the degree of elaborative encoding (Graf, Mandler, & Haden, 1982;Graf et al, 1984).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of recent experiments have suggested that newly acquired associations between normatively unrelated word pairs can influence the magnitude of priming on a word completion test (Graf & Schacter, 1985, 1987Schacter &Graf, 1986a, 1986b. In these experiments, subjects studied unrelated word pairs (WINDOW-REASON) and were then given a completion test in which some stems were paired with their study list cue (e.g., WINDOW-REA ; samecontext condition), and others were paired with some other cue (e.g., OFFICER-REA ; different-context condition).…”
Section: Experiments 2a-cmentioning
confidence: 99%